Molecular Docking Analysis of Acanthus ilicifolius Compounds Toward CUL4B-DDB1-AhR-ERα Complex Protein for Antiosteoporosis Discovery - Dhiani, Binar Asrining; Sarmoko, Sarmoko; Wahyuningrum, Retno; Yulianto, Akbar (Pharmaceutical Sciences and Research, 2023)
Osteoporosis represents a significant global public health issue, particularly among the aging population. Its incidence reaches 18.3% of the total population, with the highest prevalence observed in elderly postmenopausal women. A key factor in osteoporosis is the decreased expression level of estrogen receptor alpha (ERα), attributed to its degradation by the ubiquitin ligase protein complex Cullin4B (CUL4B), DNA damage binding 1 (DDB1), and aryl hydrocarbon receptor (AhR), collectively known as CUL4BAhR. Acanthus ilicifolius L contains compounds exhibiting antiosteoporosis activity, primarily by inhibiting osteoclastogenesis via RANKL. However, no reports exist of antiosteoporosis agents that act by inhibiting ERα degradation via CUL4BAhR. This study employed an in silico approach to predict active compounds from A. ilicifolius that could inhibit ERα degradation via CUL4BAhR, potentially developing them into antiosteoporosis agents. We utilized the 3D structures of proteins CUL4B-DDB1 (PDB ID:4A0L), AhR (5NJ8), and ERα (1A52) in various molecular docking tools, including ClusPro2.0, PyRx0.8, PyMol, PLIP, and SWISS-MODEL for QMEAN and structure assessment analysis. The ligands tested were acancifoliuside, acanthaminoside, acteoside, isoacteoside, (-)-lyoniresinol, (-)-lyioniresinol-3a-O-β-glucopyranoside, and estradiol. Acteoside displayed lower binding affinity energy (-9.7 kcal/mol) compared to estradiol (-8.9 kcal/mol) and was the lowest among all compounds. Acteoside was found to weaken the interaction between CUL4B-Rbx1 and CUL4B-DDB1 but not between AhR and ERα. Consequently, acteoside could be a viable candidate as an antiosteoporosis agent by inhibiting ERα degradation via the CUL4B-DDB1-AhR pathway. Further biochemical, in vitro, and in vivo studies are required to strengthen this evidence.